2020
DOI: 10.3390/ani10101827
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Palmitoyl-Glucosamine Co-Micronized with Curcumin Relieves Osteoarthritis Pain and Benefits Joint Mobility

Abstract: Chronic mixed pain and orthopedic dysfunction are the most frequently associated consequences of canine osteoarthritis (OA). An unmet need remains for safe and effective therapies for OA. Palmitoyl-glucosamine (PGA) and curcumin are safe and naturally occurring compounds whose use is limited by poor bioavailability. Micronization is an established technique to increase bioavailability. The aim of this study was to investigate if the dietary supplementation with PGA co-micronized with curcumin (PGA-Cur, 2:1 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…The inhibitory action of PEA against the release of cytokines is widely documented in the literature. Several studies have shown that um-PEA, as well as many of its analogues such as Adelmidrol, N-Palmitoylethanolamine-oxazoline (PEA-OXA), the oxazoline of PEA or N-Palmitoyl-D-Glucosamine (PGA), were able to decrease the plasma levels of cytokines such as TNF-α and IL-1β [ 44 , 45 , 46 , 47 , 48 ]. Furthermore, um-PEA showed protective effect in lung; in fact, it was seen that um-PEA reduced inflammation in terms of cytokines release and immune cells infiltration in model of idiopathic pulmonary fibrosis induced by bleomycin intratracheal administration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory action of PEA against the release of cytokines is widely documented in the literature. Several studies have shown that um-PEA, as well as many of its analogues such as Adelmidrol, N-Palmitoylethanolamine-oxazoline (PEA-OXA), the oxazoline of PEA or N-Palmitoyl-D-Glucosamine (PGA), were able to decrease the plasma levels of cytokines such as TNF-α and IL-1β [ 44 , 45 , 46 , 47 , 48 ]. Furthermore, um-PEA showed protective effect in lung; in fact, it was seen that um-PEA reduced inflammation in terms of cytokines release and immune cells infiltration in model of idiopathic pulmonary fibrosis induced by bleomycin intratracheal administration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, natural plant-based treatments have been developed as alternatives for numerous diseases, with fewer side effects than conventional drugs [ 16 , 17 ]. Previous studies have shown that some plant extracts have preventive effects against OA pathogenesis [ 18 , 19 ]. Cornus officinalis (CO) of the dogwood genus has been found in Eastern Asia for more than 2000 years and has been employed as a traditional natural product for maintaining liver and kidney health [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation with Palmitoyl-Glucosaine with curcumin decreased MIA-induced secondary allidynia at either threshold of latency level. Also, PGA-Cur with significantly decrease in serum levels of TNF-α, IL-1β, NGF as well as metalloproteases 1,3, and 9 [ 36 ]. In addition, there are studies on pain and inflammation ameliorate in osteoarthritis disease studies using natural compounds such as cashew nut, hyaluronic acid, and ALIAmide palmitoylglucosamine [ 21 , 22 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%